Students’ Preference of Speaking Activities in Online ESP Classes - Sartika Otodu; Khoiriyah Khoiriyah (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aims to find out the students’ preferences for online classroom activities in English for Specific Purpose (ESP) speaking skills and the benefits that the students get from their preferred activities. Eighty-five students of the Psychology Department ranging from 17 to 22 years old, were proportionally selected to involve filling in the questionnaire and 10 students were interviewed. The findings show that there were several online learning activities both in synchronous or asynchronous mode including conducting a discussion by using video conference (zoom, google meet, etc.), conducting online task or quizzes, making a self-introduction video, conducting asynchronous discussion through learning platforms (canvas/LMS, google classroom, Edmodo, etc.), watching a Youtube video, making video project about a topic, and making a video about digital storytelling. Yet, the most favourable ofthe students’ preferences of online classroom activities in ESP speaking skills is discussion activities by using video conferences such as Zoom and Google Meet (Mean=3.3). Those activities were beneficial for students to improve students’ vocabulary, creativity, and speaking skills as well. In conclusion, t     he use of video conferencing such as Zoom and Google Meet was considthe most preferable learning activities for speaking skills, followed by quizzes, watching Youtube, and other online learning activities. The students perceived that online speaking activities could improve their speaking skills. In addition, the implication of the study will be further discussed as well.